A geochemical investigation of the water and sediments of Barber's Pan, North West Province - Knesl, Oliver (Department of Geological Sciences, 2017)
Pans comprise a large proportion of southern African wetlands and yet remain poorly classified. Very little data is available on the aqueous chemistry of southern African saline systems, and with the exception of a few publications dealing, in part, with the soil and associated materials of pan floors and margins, soil and sediment information on pans is similarly limited. Barber's Pan is a shallow, alkaline lake situated in the North West Province of South Africa. It is a unique system in several respects, but is considered most valuable from the aspect of bird conservation, since it is perennial in an area characterized by shallow, seasonally filled pans. Its perennial state is the consequence of anthropogenic intervention in the early part of this century which resulted in the diversion of the Harts River back along its fossil course. The biogeographical importance of Barber's Pan is emphasised by its designation as the only RAMSAR site in the North West Province. The overall objective of this study was to provide a geochemical characterization of Barber's Pan. This was approached by reviewing pertinent literature on the origin and geochemical characteristics of pans and saline lakes through an investigation of the water and sediments of Barber's Pan. The study focused on four aspects of the pan geochemistry, namely: the levels of certain nutrients and potential pollutants in the pan; gaining an understanding of the dynamics of phosphorus, as well as other nutrients, in the pan; geochemically characterizing the sediments; and investigating the impact of evaporative concentration of the pan water on the overall geochemistry of the system. Comparative investigations were carried out on the sediments of the Harts River diversion and Leeupan, a neighbouring, actively deflational, ephemeral pan.